When men revolt and why. A reader in political violence and revolution. Ed. by J.Ch. Davies. [With contribs of Th.(G.) Masaryk, M.M. Phillips, F. Engels a.o.] (The Free Press etc., 1971)
With bibliogr., graphs and tabs.